Denunciations of Sorcery as Demonic Possession in Old Russian Izmaragd - Tufanova, Olga (Quaestio Rossica, 2023)
Old Russian scribes repeatedly tried to refute and devalue the abilities of the sorcerers in works of various genres. However, despite all attempts to instill in people a negative attitude towards sorcery, in the seventeenth century, both commoners and rulers turned for help to magicians, sorcerers, whisperers, astrologers, shamans, etc. at difficult times of their lives. A centuries-old tradition behind such appeals forced preachers to use various poetological and psychological methods of persuasion and suggestion. This article explores the rhetorical suggestive techniques and features of the argumentation system in homilies against sorcery, which are part of Izmaragd, an Old Russian collection of regulatory texts of stable composition. The author refers to The Homily of the Holy Fathers on Sorcery, a part of the 16th-century Izmaragd, and The Homily of St John Chrysostom on Those Who Are Cured of Illness by Sorcery, which is part of the Izmaragd. In 17th-century Izmaragd, The Homily of the Holy Fathers about Sorcery is part of The Homily about Those Who Are Treated by Sorcery and does not exist separately as an independent text. Therefore, referring to these texts, one can trace how the original suggestive rhetorical devices and argumentation change. The study demonstrates that in comparison with The Homily of the Holy Fathers about Sorcery, The Homily about Those Who Are Treated by Sorcery, uses a richer palette of rhetorical and psychological methods of influencing the audience. The communicative goal of convincing people to refuse to turn to sorcerers is achieved in different ways. Perhaps due to the brevity of the text itself, The Homily of the Holy Fathers on Sorcery employs simple traditional means, i. e. multiple repetitions and appeal to authority (indirect quotations). The Homily about Those Who Are Treated by Sorcery employs a different, more subtle technology of speech hypnosis in the form of direct and contextual suggestions. In addition to the rhetorical devices typical of old Russian sermons (repetitions, rhetorical questions, exclamations, appeals, comparison, etc.), the text contains an extensive system of argumentation. Appeals to authority (in particular, its subtype – appeal to fame) combine with examples that are a model of behaviour and an anti-model, as well as with maxims of a different nature (intimidating, containing promises). The two Homilies demonstrate two completely different systems of speech impact on the audience. It is unnecessary to talk about the intentional transformation of original rhetorical suggestive devices and systems of argumentation in relation to these texts. Most likely, The Homily of the Holy Fathers about Sorcery inherits the oral tradition of delivering sermons and therefore is based on simple methods of suggestion easily perceived by the ear, and The Homily about Those Who Are Treated by Sorcery, conceived as a written text, was created based on old rhetorical schools.